Preservation of Indigenous Knowledge in Indonesia: Cultural Conservation Effort - Anggraeni, Novita Cristyne; Tamara Adriani Salim; Muhammad Prabu Wibowo (Program Studi Ilmu Perpustakaan UIN Alauddin, 2024)
Indigenous knowledge is the knowledge owned by local communities that needs to be preserved and passed down from generation to generation. The objective of this research is to analyze preserving indigenous knowledge in Indonesia based on the World Bank's process of preserving indigenous knowledge. Data for this research were obtained from journal articles on the preservation of indigenous knowledge in Indonesia, published between 2017 and 2023, obtained from GARUDA, Google Scholar, and ProQuest journals. This study has undertaken a systematic literature review using the PICOC methodology. The outcomes explain that the types of indigenous knowledge in Indonesia consist of various categories, namely language, arts, architecture, oral culture, and customs. The study also indicates that in the preservation stage, indigenous knowledge has reached the recognition and validation phase. However, it is still not optimal in implementing other stages, namely recording and documentation, storage, transfer, and dissemination. The results also show that in the process of preserving local knowledge, the tools and techniques used are mobile phones, cameras, computers, social media, online databases, books, photo collections, CDs, and websites.